PERAN BANK INDONESIA DALAM PENGEMBANGAN TRANSAKSI UANG DIGITAL - Nur Riadoh Rangkuti; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This review examines the strategic role of Bank Indonesia (BI) in encouraging the adoption and development of digital currency transactions in Indonesia. Through various initiatives, BI aims to create a digital transaction ecosystem that is safe, efficient and inclusive. Bank Indonesia plays an active role in educating the public about the use of digital money, increasing digital literacy, and building trust in digital transactions. Through this multilateral role, BI aims to encourage the growth of digital currency transactions in Indonesia which is expected to increase efficiency, inclusiveness and competitiveness of the national economy.